2014
DOI: 10.5152/kd.2012.35
|View full text |Cite
|
Sign up to set email alerts
|

Cheyletiella Dermatitis: A Case Report

Abstract: ÖzetCheyletiella kedi, köpek ve tavşanların derisinde yaşayan bir akar cinsi olup yüksek oranda bulaşıcılığa sahiptir. İnfeste hayvanlarda kaşıntı ve kepeklenme şeklinde hastalığa yol açabilir, ancak sıklıkla asemptomatik olduğundan parazitten şüphelenilmedi-ği takdirde tanı koymak güçtür. İnfeste hayvan sahiplerinin de %2'si infeste olmaktadır. Dermatoz, insanlarda infeste hayvanla temas eden bölgelere özgü eritemli, kaşıntılı, bazıları nekrotik özellikte papüller şeklinde görülmektedir. Bu olgu sunumunda inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…It was stated that this mite could be a possible vector of myxomatosis in rabbits (34). Three reports were related to cheyletiellosis in humans in Turkey; one etiologic agent was Cheyletiella blakei (35) and one was Cheyletiella parasitivorax (36), and in the other the Cheyletiella species was not identified (37). It was reported that C. parasitivorax has been found in the highest prevalence in wild rabbits (1,2).…”
Section: Discussionmentioning
confidence: 99%
“…It was stated that this mite could be a possible vector of myxomatosis in rabbits (34). Three reports were related to cheyletiellosis in humans in Turkey; one etiologic agent was Cheyletiella blakei (35) and one was Cheyletiella parasitivorax (36), and in the other the Cheyletiella species was not identified (37). It was reported that C. parasitivorax has been found in the highest prevalence in wild rabbits (1,2).…”
Section: Discussionmentioning
confidence: 99%